Molecular Characterization of Haemaphysalis Species and a Molecular Genetic Key for the Identification of Haemaphysalis of North America - Thompson, Alec T.; Dominguez, Kristen; Cleveland, Christopher A.; Dergousoff, Shaun J.; Doi, Kandai; Falco, Richard C.; Greay, Telleasha; Irwin, Peter; Lindsay, L. Robbin; Liu, Jingze; Mather, Thomas N.; Oskam, Charlotte L.; et al. (Frontiers in Veterinary Science, 2020)
Haemaphysalis longicornis (Acari: Ixodidae), the Asian longhorned tick, is native to East Asia, but has become established in Australia and New Zealand, and more recently in the United States. In North America, there are other native Haemaphysalis species that share similar morphological characteristics and can be difficult to identify if the specimen is damaged. The goal of this study was to develop a cost-effective and rapid molecular diagnostic assay to differentiate between exotic and native Haemaphysalis species to aid in ongoing surveillance of H. longicornis within the United States and help prevent misidentification. We demonstrated that restriction fragment length polymorphisms (RFLPs) targeting the 16S ribosomal RNA and the cytochrome c oxidase subunit I (COI) can be used to differentiate H. longicornis from the other Haemaphysalis species found in North America. Furthermore, we show that this RFLP assay can be applied to Haemaphysalis species endemic to other regions of the world for the rapid identification of damaged specimens. The work presented in this study can serve as the foundation for region specific PCR-RFLP keys for Haemaphysalis and other tick species and can be further applied to other morphometrically challenging taxa.